PENILAIAN DAUR HIDUP BOTOL GELAS PADA PRODUK MINUMAN TEH - Mohammad Yani, Endang Warsiki, dan Noviana Wulandari TIP (Department of Agroindustrial Technology, Bogor Agricultural University, 2014)
ABSTRACT Glass bottle is used as packaging for beverage product to keep its quality. The objectives of this study were life cycle assessment (LCA) of glass bottle, environmental impact assessment, and recycling cost analysis. The research was started from inventory analysis of glass bottle production, tea beverage industry, and recycling of glass waste, and data processing. The life cycle of glass bottle was observed as cycling from glass bottle production, tea beverage industry, consumer, cullet recycling, and come back to glass bottle production. The inventory analysis was observed at all steps. The glass bottle production occurred from mixing materials, melting, moulding, and cooling. The tea beverage industry operates glass bottle washing, filling, packing, and distributing to consumer. The glass bottle can be refilled up to 20 times. The glass recycling was started from collection, separation, size reduction to cullet, washing and drying. The cullet was added about 40%-60% of total raw materials for production of new glass bottle. The glass bottle production and recycling cullet caused environmental impact. The environmental impact assessment of bottle glass production indicated that effluent of wastewater and ambient air quality passed to standard regulation limit, in exception of total particulate matter and sulfur dioxide. The cullet recycling process produced water pollution to surface water. The glass bottle production produced air pollution. The recycling and production of glass bottle need high cost, caused by raw materials and a lot of energy requirement for washing, melting silica and cullet, so the glass bottle price was relatively more expensive. Keyword: life cycle assessment, glass bottle, inventory analysis, recycle, environmental impact assessment, cost analysis